Emotional Beat: Deepening Dance Expression and Creativity - Mansyur, Herlinda; Elizar, Elizar; Mikaresti, Pamela (Gondang: Jurnal Seni dan Budaya, 2025)
Dance as a form of cultural expression has become the primary medium for communicating human emotions in a unique and comprehensive way. The purpose of this paper is to explore the relationship between emotional expression and creativity in dance, focusing on the methods and techniques used in the literature review. This paper describes how dance artists portray and utilize emotions in their work. Through the literature review method, it explores the various approaches used by artists to express emotion authentically and move the audience. The results of this study highlight the importance of an in-depth understanding of the psychology of emotions and the dance techniques used to achieve specific expressive goals. Further developing an understanding of how the expression of emotion in dance can influence the aesthetic experience of the audience and support the creativity of the artist. Contribution to broadening the horizons of the importance of emotional beats in dance, illustrating how literature review can be an effective tool for exploring the complexities of human expression through movement and rhythm.